Combustion and Sooting Behavior of Spark-Ignited Ethanol-Isooctane Sprays under Stratified Charge Conditions - Storch, Michael; Pfaffenberger, Andreas; Kögl, Matthias; Will, Stefan; Zigan, Lars (Energy & Fuels, 2016)
A spray combustion investigation within an optically accessible high-temperature/high-pressure chamber with ignition was conducted to study soot formation of ethanol blended fuels at cold start conditions. The fuels ethanol, isooctane, and its blends E85 (85 vol% of ethanol in isooctane) and E20 were studied at different temperatures under direct injection spark ignition engine stratified charge conditions. A high-speed camera in combination with an image stereoscope was used in order to visualize the combustion in two different wavelength regions simultaneously to distinguish between premixed and sooting combustion. Additionally, a spectroscopic setup was applied for detailed flame emission analysis on high time-resolved scale. Furthermore, a spray formation investigation was carried out in order to evaluate the fuel evaporation process. The study reveals that depending on the operation conditions either the chemical or the physical processes dominate the combustion and sooting behavior. At low ambient temperature (473 K at 0.8 MPa air pressure) fuel blends with high ethanol content show reduced soot luminosity despite of the delayed evaporation and mixture formation. For E20 stronger soot radiation intensities than for isooctane were found, indicating that the physical fuel properties are governing the soot formation. An increase of gas temperature (673 K) reduces the intensity of soot luminosity for all fuels due to faster evaporation and lower probability of droplet combustion. The soot radiation decreases with increasing ethanol content. The results show that at the high gas temperature condition the physical fuel properties, especially the enthalpy of evaporation, are less important, but chemical effects dominate soot formation.